SUBSTITUTION OF FERMENTED DUCKWEED MEAL (Lemna Sp.) AS AN ALTERNATIVE PROTEIN SOURCE SOYBEAN MEAL IN SUPPORTING THE GROWTH OF TILAPIA (Oreochromis niloticus) - Yusup, Maulid Wahid; Atmaja, Purwa Septi Diah Ayu Kusuma; Santoso, Limin; Elisdiana, Yeni (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2021)
Tilapia (Oreochromis niloticus) is a freshwater fish commodity that has high economic value, is widely cultivated and has high demand. However, the obstacle that is often experienced by farmers is the high price of feed caused by the high price of imported feed raw materials. Overcoming this can be done by looking for alternative raw materials that can replace soybean meal flour such as fermented lemna flour. This research was conducted to study the growth performance of tilapia fed a test feed using fermented lemna flour (Lemna sp.) substitution. The total treatment used was 5 treatments and 3 replications, with a completely randomized design (CRD). Treatment A (0% TLF), B (25% TLF), C (50% TLF), D (75% TLF), and treatment E (100% TLF). Parameters observed were absolute weight gain, daily growth rate, protein retention, feed conversion, protein efficiency ratio, survival rate, and water quality. The results showed that treatment B (25% TLF) gave the best results compared to other treatments, where the absolute weight growth rate reached 7.11 g, the daily growth rate (SGR) was 3.39%, feed conversion (FCR) was 2.22 and protein retention 36.08%.